SMRT-Cappable-seq reveals complex operon variants in bacteria - Bo Yan (Nature Portfolio, 2018)
Fragmentation of transcripts can hide operon complexity in genome-wide transcriptome sequencing. Here the authors sequenced a prokaryotic transcriptome using PacBio and provide insights into operon structure and read-through at termination sites.